Rosa canina L. improves learning and memory-associated cognitive impairment by regulating glucose levels and reducing hippocampal insulin resistance in high-fat diet/streptozotocin-induced diabetic rats - ERTAŞ, BÜŞRA; YAVUZ, AYŞE NUR; TAŞKIN, TURGUT; ÇAM, MUHAMMET EMİN (My University, 2023)
Ethnopharmacological relevance: Recent studies claim that Type-2 diabetes mellitus (T2DM) and Alzheimer\"s disease (AD) overlap in several common pathological pathways which from neuronal damage to impaired memory performance. It is known that the use of Rosa canina L. (R. canina) as medicine in folk medicine dates back to ancient times and is used in the treatment of nervous diseases in Persian medicine. However, the effect of R. canina on diabetes-related cognitive decline and memory impairment has not yet been studied. Aim of the study: We evaluated the impact of T2DM on AD-like alterations and examined the molecular mechanism of a possible effect of R. canina on cognitive alterations in diabetic rats. Materials&methods: R. canina ethanol extract was obtained by maceration method. This study was performed with male Sprague-Dawley rats fed with a high-fat diet (HFD) for 8 weeks, low-dose streptozotocin (STZ; 35 mg/kg IP) injection for 4 weeks, and R. canina (250 mg/kg; per oral) and metformin (400 mg/kg; per oral) administration for 4 weeks. The weight and blood glucose of rats were measured weekly. To evaluate glucose tolerance area under the curve (AUC) was calculated by performing an oral glucose tolerance test. Then the rats were subjected to behavioural tests, and their hippocampus and cortex tissues were obtained for biochemical and morphological analyses. Results: R. canina could manage glucose responsiveness by reducing post-prandial blood glucose levels, preventing weight loss, and raising serum insulin levels in T2DM-induced rats. Behavioural tests showed that R. canina significantly improves diabetes-related cognitive decline in recall and long-term memory. Treatment with R. canina significantly reversed HFD/STZ-induced increases in insulin, amyloid-β, amyloid precursor protein levels, and acetylcholinesterase activity in the prefrontal cortex and hippocampus. Furthermore, histological analyzes revealed the protection of R. canina against neuronal disruption in the cortical and hippocampal CA3 region caused by chronic hyperglycemia. Conclusion: Analyzed collectively, these results suggest that R. canina can correct T2DM-related cognitive decline may be attributed to insulin pathway modulation, prevention of amyloid deposition, and increased cholinergic transmission.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; MOLECULAR BIOLOGY & GENETICS; PHARMACOLOGY & PHARMACY; BIOCHEMISTRY & MOLECULAR BIOLOGY; Farmakoloji; İlaç Keşfi; Pharmacology; Drug Discovery; Alzheimer's disease; Cognitive impairment; Insulin signaling; Type-2 diabetes mellitus